2016
DOI: 10.1016/j.molcel.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin F-Mediated Degradation of SLBP Limits H2A.X Accumulation and Apoptosis upon Genotoxic Stress in G2

Abstract: Summary SLBP (stem-loop binding protein) is a highly conserved factor necessary for the processing, translation, and degradation of H2AFX and canonical histone mRNAs. We identified the F-box protein cyclin F, a substrate recognition subunit of an SCF (Skp1-Cul1-F-box protein) complex, as the G2 ubiquitin ligase for SLBP. SLBP interacts with cyclin F via an atypical CY motif, and mutation of this motif prevents SLBP degradation in G2. Expression of an SLBP stable mutant results in increased loading of H2AFX mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 52 publications
4
66
0
Order By: Relevance
“…Notably, proteasomal degradation of SLBP in G2 is restricted to vertebrates and evolutionary correlates with the occurrence of SCF cyclin F complexes. 10 As mentioned earlier, SLBP degradation in G2 was also attributed to the activity of CRL4 WDR23 .…”
Section: Mechanistic Consequences Of Non-proteolytic Slbp Monoubiquitmentioning
confidence: 66%
“…Notably, proteasomal degradation of SLBP in G2 is restricted to vertebrates and evolutionary correlates with the occurrence of SCF cyclin F complexes. 10 As mentioned earlier, SLBP degradation in G2 was also attributed to the activity of CRL4 WDR23 .…”
Section: Mechanistic Consequences Of Non-proteolytic Slbp Monoubiquitmentioning
confidence: 66%
“…Hence, these elegant studies from the Pagano group together revealed a synergy between CRL2 FEM1A/B/C and SCF Cyclin F to orchestrate the timely degradation of SLBP during the G1 and G2 phases, 6,7 respectively, thereby synchronizing histone and nucleosome metabolism with cell cycle progression (Fig. 1).…”
mentioning
confidence: 98%
“…At the end of S phase, SLBP is phosphorylated at Thr-61 and Thr-62 by CK2 and cyclin A2-CDK1, 4,5 respectively, facilitating its degradation by SCF Cyclin F in the following G2 phase, which is largely dependent on an atypical RxL motif present in SLBP. 6 Interestingly, there is evidence that SLBP may also be degraded during the G1 phase when Cyclin F is not abundantly expressed. However, the E3 ligase responsible for its decay in G1 phase remained elusive until this report.…”
mentioning
confidence: 99%
See 2 more Smart Citations